Non-linearity in ecosystem services: temporal and spatial variability in coastal protection - Koch, Evamaria W. (2009)
Natural processes tend to vary over time and space, as well as between species. The ecosystem services these natural processes provide are therefore also highly variable. It is often assumed that ecosystem services are pro- vided linearly (unvaryingly, at a steady rate), but natural processes are characterized by thresholds and limit- ing functions. In this paper, we describe the variability observed in wave attenuation provided by marshes, mangroves, seagrasses, and coral reefs and therefore also in coastal protection. We calculate the economic con- sequences of assuming coastal protection to be linear. We suggest that, in order to refine ecosystem-based man- agement practices, it is essential that natural variability and cumulative effects be considered in the valuation of ecosystem services.